THE CONTRIBUTION INCOME, INVESTMENT RESULTS, AND CLAIM EXPENSES ON SHARIA LIFE INSURANCE INCOME - Nainggolan, Laila Mardiyah; Soemitra, Andri (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2020)
This study aims to examine the effect of Contribution Income Investment Results and Claim Expenses on Sharia Life Insurance Profits in Indonesia for the 2012-2019 period. This research is a quantitative study with secondary data in the form of Islamic financial reports and the sample selection using purposive sampling. The amount of data is 13 companies with eight years of observation to obtain 104 observational data which are sampled in this study. The technique used is panel data regression analysis technique, with analysis of hypothesis testing, namely the t test and F test. The results show that contribution income partially affects the profit of Islamic life insurance, the investment results also affects the profit of Islamic life insurance, if the fund invested are large, the investment returns will be large so that the profit will be high. Furthermore, claim expense partially affects the profit of sharia life insurance, the claims will reduce the amount of funds to be invested by the company, at the end it reduces the company's profit. Based on F test, all variables simultaneously influence the profit of Islamic life insurance. The suggestion is that, in order to increase the profitability of Islamic insurance, the company Islamic insurance needs to consider the investment process, also to increase the underwriter analysis to mitigate the excess of expenses from claims.